2012
DOI: 10.1186/2046-9063-8-28
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal distribution, diel vertical distribution and feeding behavior of Paraeuchaeta concinna in the shallow subtropical coastal waters of eastern Hong Kong

Abstract: BackgroundPredatory copepods of the family Euchaetidae are widely distributed in polar, temperate, subtropical and tropical oceans. Paraeuchaeta concinna is the most abundant Euchaetidae in the subtropical coastal seas of Hong Kong and southern China. However, compared to Euchaetidae species in temperate and polar regions, relatively little information is available on the ecology of P. concinna and other Euchaetidae species in the subtropical oceans. This paper provides information on the seasonal abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…In addition, the appearance of larger copepods in the outer part of Tolo Harbour during winter and spring may be due to the introduction of large non-native species from offshore waters. The large calanoid copepods Calanus sinicus (Hwang & Wong, 2005;Zhang & Wong, 2013) and Paraeuchaeta concinna (Wong et al, 2012) have been shown to appear in the coastal seas of eastern Hong Kong waters during late winter and early spring only. Table 1.…”
Section: Spatial and Seasonal Variationsmentioning
confidence: 99%
“…In addition, the appearance of larger copepods in the outer part of Tolo Harbour during winter and spring may be due to the introduction of large non-native species from offshore waters. The large calanoid copepods Calanus sinicus (Hwang & Wong, 2005;Zhang & Wong, 2013) and Paraeuchaeta concinna (Wong et al, 2012) have been shown to appear in the coastal seas of eastern Hong Kong waters during late winter and early spring only. Table 1.…”
Section: Spatial and Seasonal Variationsmentioning
confidence: 99%
“…Euchaeta rimana is a subtropical, open-ocean copepod common in the plankton of North Pacific central gyre (Yen et al, 1991). The abundance of E. rimana is maximum in the oceanic waters of eastern and southeastern Hong Kong (Wong et al, 2012). This species is found in the East China Sea, where water temperature and salinity are high, supposed to be influenced by warm Kuroshio Water (Zue et al, 2006;Tseng et al, 2008).…”
Section: Co-occurring Species and Environmental Factormentioning
confidence: 99%
“…This downward movement may heighten predation risk by exposing prey species to deep-dwelling predators. These seasonal oscillations can substantially alter the pattern of distribution (Burns and Mitchell, 1980;Primicerio, 2000;Wong et al, 2012) and compel organisms to occupy suboptimal depths at the expense of their overall fitness (Gliwicz, 1986;Lampert, 1993;. The vast majority of deep African tropical lakes are permanently stratified with muted seasonality of their water columns (MacIntyre, 2012).…”
Section: Introductionmentioning
confidence: 99%